A Rare Simultaneous Detection of a Mid‐Latitude Plasma Depleted Structure in O(1D) 630.0 and O(1S) 557.7 nm All‐Sky Airglow Images on a Geomagnetically Quiet Night - D. Patgiri; R. Rathi; V. Yadav; D. Chakrabarty; M. V. Sunil Krishna; S. Kannaujiya; P. Pavan Chaitanya; A. K. Patra; Jann‐Yenq Liu; S. Sarkhel (Geophysical Research Letters)
Abstract This letter reports first simultaneous detection of F‐region plasma‐depleted structure in O(1D) 630.0 and O(1S) 557.7 nm airglow images on a geomagnetically quiet‐night (Ap = 3) of 26 June 2021 from mid‐latitude station (Hanle, India) due to enhanced thermospheric 557.7 nm emission. Since nighttime thermospheric 557.7 nm emission over mid‐latitudes is predominantly masked by significantly larger mesospheric component, F‐region plasma structures are rarely observed in 557.7 nm images. Interestingly, thermospheric 557.7 nm emission was not significant on the following geomagnetically quiet‐night as bands of medium‐scale traveling ionospheric disturbance were only observed in 630.0 nm images. Poleward wind generated by Equatorial Temperature and Wind Anomaly transported plasma from the boundary of equatorial ionization anomaly, causing significant electron density enhancement around 250 km and descent of F‐layer peak over Hanle on 26 June 2021. This amplified the dissociative recombination enabling the simultaneous detection of plasma‐depleted structure in 557.7 and 630.0 nm images.